Fish diversity and heavy metal content mercury (Hg), arsenic (As) on the water and fish in Cikaniki river, Bogor regency - Mia Azizah; Gladys Ayu Paramitha K.W (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Organisms that live in waters are sensitive to changes in the water quality in which they live. The quality of the water in the Cikaniki River is threatened by the gold mining industry, illegal mining, agricultural activities, and settlements. One of the organisms that will be affected by these environmental changes is fish. This research aims to obtain a diversity index of fish species and to determine the content of heavy metals Mercury (Hg), Arsenic (As) on the water, and fish. Research on the diversity of fish in Cikaniki River, Bogor Regency, was carried out in January–March 2020. The research was conducted at five selected stations, and each station carried out three times the sampling of fish and water. The metal content test process is carried out at the Chemical Laboratory of the University of Nusa Bangsa. The research instrument used was the observation sheet for fish identification and heavy metal content. Fish identification was carried out at the Faculty of Mathematics and Natural Sciences Laboratory, University of Nusa Bangsa. Identification use characteristics observed included body shape, body length height, color pattern, muzzle shape, fin shape, number of fins, and tail shape. Calculation of heavy metals using an ICP–OES (Inductively Coupled Plasma) tool. This research found seven fish species in the Cikaniki river; based on its dominance, four types of fish dominate: Nemacheilus chrysolaimos, Puntius bionotatus, Channa striata, and Glyptothorax platypogonides. The content of heavy metal mercury (Hg) in water is still below the standard quality threshold, while the Hg content in fish is above the quality standard with a value range of 0.5 - 1.09 mg/kg. The content of heavy metal Arsenic (As) in water ranges from 0.02 - 0.6 mg/L, with the highest value found at stations 4 (irrigation canals), As in the highest fish at stations 1 and 2 with a value range of 1-1.1 mg/kg. The conclusion of this research is that there are seven species of fish and fish in the Cikaniki river which contain high Hg and As heavy metals.